Replacement of multiyear sea ice and changes in the open water season duration in the Beaufort Sea since 2004. Issue 3 (19th March 2016) - Galley, R. J.; Babb, D.; Ogi, M.; Else, B. G. T.; Geilfus, N.‐X.; Crabeck, O.; Barber, D. G.; Rysgaard, S.
Abstract: The last decade has witnessed the nine lowest Arctic September sea ice extents in the observational record. It also forms the most recent third of the long‐term trend in that record, which reached −13.4% decade −1 in 2015. While hemispheric analyses paint a compelling picture of sea ice loss across the Arctic, the situation with multiyear ice in the Beaufort Sea is particularly dire. This study was undertaken in light of substantial changes that have occurred in the extent of summer multiyear sea ice in the Arctic inferred from the passive microwave record. To better elucidate these changes at a sub‐regional scale, we use data from the Canadian Ice Service archive, the most direct observations of sea ice stage‐of‐development available. We also build upon the only previous sea ice climatological analysis for Canada's western Arctic region by sea ice stage‐of‐development that ended in 2004. The annual evolution of sea ice by stage of development in Canada's western Arctic changed dramatically between 1983 and 2014. The rate of these changes and their spatial prevalence were most prominent in the last decade. In summer, total sea ice loss occurred via reductions in old and first‐year sea ice over increasingly large areas and over more months per year. Resultant delay of thermodynamic freeze up has increased the annual open water duration in the study region. The winter sea ice cover was increasingly composed of first‐year sea ice at the expense of old ice. Breakup timing has not significantly changed in the region. Key Points: Replacement of old sea ice by first‐year sea ice in the Beaufort Sea is quantified Delayed freeze up, not breakup timing, is responsible for lengthened summer open water duration Increased first‐year sea ice may be affecting the formation of the Cape Bathurst flaw lead polynya